The benefit and impact of servant leadership on organizational culture, rewards, job satisfaction, and employee performance - Handayani Rahmaya Nova; Indrayanto Adi; Arif Aryadi; Suandika Made (BIO Web of Conferences)
This research examines the influence of Servant Leadership on Organizational Culture and Rewards and its impact on Job Satisfaction and Employee Performance. This research uses a survey method at PT. BTN (Persero) Tbk. with a sample of 169 respondents. The analytical tool used is Generalized Structural Component Analysis (GSCA). The main finding in this research is that Servant Leadership has an insignificant direct effect on Employee Performance but indirectly has a significantly positive effect through Organizational Culture, Rewards, and Job Satisfaction. Recommendations to PT BTN (Persero) Tbk. include improving Servant Leadership by encouraging leaders with task orientation, improving organizational culture by encouraging employee professionalism, fostering high rewards by creating a reward system, especially intrinsic rewards that are able to accommodate employees’ personal growth, increasing job satisfaction by formulating satisfaction with employee opportunities/promotions, increasing employee performance by formulating personal characteristics as the main measurement.